The Relationship Of Knowledge And Attitude Of Breastfeeding Mothers Towards Exclusive Breastfeeding - Simarmata, Mesrida; Dewi, Rini Senza; Putri, Ninsah Mandala; Hutahaean , Nurmalina (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Background : Breast milk is the best food for babies 0-6 months. Exclusive breastfeeding coverage is still low in Indonesia. Many factors become obstacles to exclusive breastfeeding. Method : This research uses a correlation study design cross sectional, to look for the relationship between knowledge and attitudes towards exclusive breastfeeding. The population is all mothers who have babies aged 6-24 years in Sisumut Village in 2023, totaling 50 mothers using a purposive sampling technique. Research time May 2023 in Sisumut Village. Data is taken primarily for knowledge and attitudes. Questionnaire instrument tool using interview method. The data analysis technique uses Chi statistical test analysis Squere . Results : The majority of respondents had less than 76% knowledge, 54% agreed, 76% aged 20-35 years, 44% SMS education and 66% employed. There is a relationship between knowledge and exclusive breastfeeding, namely p = 0.002 < of α value = 0.05. There is no relationship between attitude and exclusive breastfeeding, namely p= 0.145 > than α value = 0.05. Conclusion : There is a relationship between knowledge and no relationship between attitudes and exclusive breastfeeding. It is best to be given support from health workers, family and the mother's intention to provide exclusive breastfeeding